2006
DOI: 10.1007/s11244-006-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 2-dimensional platinum nanocatalyst arrays by electron beam lithography: ethylene hydrogenation and CO-poisoning reaction studies

Abstract: Electron beam lithography (EBL) has been used to fabricate platinum nanoparticle arrays in the 20-nm size range on oxide thin films of silica and alumina deposited onto silicon wafers. A combination of characterization techniques (SEM, AFM, XPS, AES) has been used to determine size, spatial arrangement and cleanliness of these fabricated catalysts. Ethylene hydrogenation reaction studies have been carried out over these platinum nanoarrays and have revealed major differences in turnover rates and activation en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…In this context, we have for several years been developing the synthesis of nanoparticles using an organometallic approach. [5] Pioneering 13 C MAS (magic angle spinning) NMR spectroscopy has shown the coordination of CO on ruthenium nanoparticles (Ru NPs) to occur in three different modes: terminal, bridging and multicarbonyl. It also allows the tuning of their surface chemistry through addition of ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have for several years been developing the synthesis of nanoparticles using an organometallic approach. [5] Pioneering 13 C MAS (magic angle spinning) NMR spectroscopy has shown the coordination of CO on ruthenium nanoparticles (Ru NPs) to occur in three different modes: terminal, bridging and multicarbonyl. It also allows the tuning of their surface chemistry through addition of ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Recent HP-XPS studies [16] utilizing such approaches have proven illuminating in investigating the effects of ambient reaction conditions on the surface composition and catalysis of alloy nanoparticles with carefully prepared core-shell structures. Additionally, investigators have employed lithography-based approaches [17][18][19][20][21] to generate surfaces containing arrays of well-defined nanoparticles, allowing a level of control over factors such as nanoparticle size and even interparticle distance. Investigations have demonstrated these surfaces can effectively simulate reaction kinetics observed on single crystal and supported catalyst surfaces [17,20,21] and have been employed to study catalysis in different types of reaction environments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated the fabrication of noble metal ͑Ag, Au, Pt͒ NPs and nanowires by EBL. 13,[15][16][17] The optical properties, especially LSPR, of EBL-derived Ag NPs have been widely characterized using optical microscopy and spectroscopy at micrometer and submicrometer resolution. Corrigan et al 13 studied the fluorescence enhancement on periodic Ag NP arrays and reported greater relative enhancement for triangular-shaped NPs compared to square-shaped ones.…”
Section: Introductionmentioning
confidence: 99%